Biodegradable Patches for Arterial Reconstruction Modified with RGD Peptides: Results of an Experimental Study - Sevostianova V. V. Victoria Victorovna; Antonova L. V. Larisa Valerjevna; Mironov A. V. Andrey Vladimirovich; Yuzhalin A. E. Arseny Evgenjevich; Silnikov V. N. Vladimir Nikolaevich; Glushkova T. V. Tatjyana Vladimirovna; Godovikova T. S. Tatyana Sergeevna; Krivkina E. O. Evgeniya Olegovna; Bolbasov E. N. Evgeny Nikolaevich (2020, 2020)
Title screen